2021
DOI: 10.1111/ecc.13505
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up after breast cancer: Variations, best practices, and opportunities for improvement according to health care professionals

Abstract: Objective: Follow-up after breast cancer can be divided into surveillance and aftercare. It remains unclear how follow-up can ideally be organised from the perspective of health care professionals (HCPs). The aim of this study was to gain insight in the organisation of follow-up in seven Dutch teaching hospitals and to identify best practices and opportunities for improvement of breast cancer (all stages) follow-up as proposed by HCPs.Methods: Semi-structured in-depth group interviews were performed, one in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…We planned to recruit at least 15 patients to achieve data saturation [13]. In the Netherlands, early stage breast cancer patients (M0) are mostly surgically treated and therefore followed by the surgery department (by a surgical oncologist or a nurse practitioner from the surgery department) for surveillance [14]. Therefore, we recruited patients by contacting the surgery departments of the participating hospitals.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…We planned to recruit at least 15 patients to achieve data saturation [13]. In the Netherlands, early stage breast cancer patients (M0) are mostly surgically treated and therefore followed by the surgery department (by a surgical oncologist or a nurse practitioner from the surgery department) for surveillance [14]. Therefore, we recruited patients by contacting the surgery departments of the participating hospitals.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…The large overestimation by GPs could be due to a knowledge-gap on the effects of different therapies, experience with estimating risks for LRR due to a small number of patients with breast cancer in their practice, and the use of prediction models. GPs are currently hardly actively involved in surveillance after breast cancer [ 10 ]. However, this may change as follow-up shifts more towards a patient-led flexible model.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that shared decision-making about personalised surveillance is desirable [ 10 , 12 ]. General overestimations of the risk for LRR might hinder objective patient information which is required for shared decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…HCPs were selected based on their role in the follow‐up care process. Through an earlier assessment in each of the Santeon hospitals (Ankersmid et al, 2021), the researchers had knowledge on which specialisms were specifically involved in surveillance for breast cancer patients. In each hospital, one or two HCPs of the involved specialisms were approached for an interview (in total 24 HCPs).…”
Section: Methodsmentioning
confidence: 99%
“…The INFLUENCE‐nomogram is a validated prognostic model to calculate the 5‐year risk for locoregional recurrences (LRRs) after breast cancer (Voelkel et al, 2019; Witteveen et al, 2015) and second primary breast tumours (Völkel et al, 2021), based upon characteristics such as TNM stage, receptor status and adjuvant treatment. Although the INFLUENCE‐nomogram has been available for some years now its uptake in clinical practice is limited (Ankersmid et al, 2021) and little is known about how this nomogram can best be used in clinical practice and on how HCPs feel about using patients' estimated personal risk for LRRs as part of the SDM process on surveillance.…”
Section: Introductionmentioning
confidence: 99%